2022
DOI: 10.3390/vaccines10060963
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Sudan ebolavirus to Support Medical Countermeasure Development

Abstract: Sudan ebolavirus (SUDV) is one of four members of the Ebolavirus genus known to cause Ebola Virus Disease (EVD) in humans, which is characterized by hemorrhagic fever and a high case fatality rate. While licensed therapeutics and vaccines are available in limited number to treat infections of Zaire ebolavirus, there are currently no effective licensed vaccines or therapeutics for SUDV. A well-characterized animal model of this disease is needed for the further development and testing of vaccines and therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Median time to death was one day quicker (Day 8 versus Day 9), clinical chemistry abnormalities and evidence of coagulopathy were more frequent one day earlier in EBOV exposed animals, body temperatures peaked earlier, and sGP was found in the serum of all animals earlier; serum viral load was similar between the two models Table 8 [ 19 ]. In addition, the results of this study are comparable to other studies modeling disease post intramuscular exposure to SUDV, in cynomolgus and rhesus macaques, including similar times to death [ 25 , 33 ]. High viral load, coagulopathy, abnormal clinical chemistry values (e.g., ALT, ALP, GGT, BUN), bleeding, and petechia have been observed in other related models [ 25 , 33 ].…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Median time to death was one day quicker (Day 8 versus Day 9), clinical chemistry abnormalities and evidence of coagulopathy were more frequent one day earlier in EBOV exposed animals, body temperatures peaked earlier, and sGP was found in the serum of all animals earlier; serum viral load was similar between the two models Table 8 [ 19 ]. In addition, the results of this study are comparable to other studies modeling disease post intramuscular exposure to SUDV, in cynomolgus and rhesus macaques, including similar times to death [ 25 , 33 ]. High viral load, coagulopathy, abnormal clinical chemistry values (e.g., ALT, ALP, GGT, BUN), bleeding, and petechia have been observed in other related models [ 25 , 33 ].…”
Section: Resultssupporting
confidence: 84%
“…In addition, the results of this study are comparable to other studies modeling disease post intramuscular exposure to SUDV, in cynomolgus and rhesus macaques, including similar times to death [ 25 , 33 ]. High viral load, coagulopathy, abnormal clinical chemistry values (e.g., ALT, ALP, GGT, BUN), bleeding, and petechia have been observed in other related models [ 25 , 33 ]. In a rhesus model of infection, an animal also survived exposure and exhibited transient or less severe disease manifestations, not unlike what was observed in the study described herein [ 33 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…For this reason, BARDA recently supported two natural history studies to characterize the progression of either MARV or SUDV in cynomolgus macaques. Both natural history studies included clinical observations of body weight, viremia, hematology, clinical chemistry, and coagulation and continuous body-temperature monitoring [ 30 , 44 ]. Overall, these natural history studies confirmed the reproducibility and utility of cynomolgus macaques as animal models for MARV and SUDV and will be useful in evaluating future medical countermeasures for these pathogens.…”
Section: Barda Investments For Filovirus Vaccine Development and Prep...mentioning
confidence: 99%